Anne Frank - Agrimbau, Diego (Graphic library., 2018)
Presents a graphic novel adaptation of Anne Frank's diaries highlighting her experiences living in hiding with her Jewish family during World War II. Includes a glossary, text-related questions, writing prompts, and resources for further information.